Routing Optimization for Wireless Sensor Network Based on Cloud Adaptive Particle Swarm Optimization Algorithm - Xu Bao (Institute of Advanced Engineering and Science, 2013)
One of the most important targets of routing algorithm for Wireless Sensor Network (WSN) is to prolong the network lifetime. Aimed at the features of WSN, a new routing optimization approach based on cloud adaptive particle swarm optimization algorithm is put forward in this paper. All paths appear at the same time in one round are fused in one particle, and the coding rule of particle is set down. The particle itself is defined as its position, the number of replaceable relay nodes in paths is defined as the velocity of particle. Cloud algorithm is used to optimize the inertia weight of particle. Optimize rules are laid out, and both residual energy of nodes and variance of all paths’ length are considered in objective function. Simulations find out the best value of balance factor in objective function, also prove that this approach can control the energy consumption of network, enhance the viability of nodes, and prolong the lifetime of network. DOI: http://dx.doi.org/10.11591/telkomnika.v11i11.3486